Cognition of Korean-English secondary school teachers about intercultural dimension in EFL teaching - Choi, Yuri (2016)
The importance of intercultural competence in education has been recognized in order to promote students’ tolerance and empathy towards others in the globalized world. Being the first and foremost foreign language subject in Korea, English classroom is considered to be the right place to address different cultures and the intercultural competence. Then, how English teachers understand intercultural competence would be important since it would greatly affect their teaching. The aim of this study is to investigate how Korean-English secondary school teachers understand intercultural dimension in EFL teaching in relation to their teaching context; and how their reported practices look like. 37 teachers participated in online survey (Google Forms) with closed and open questions. The quantitative data were used to describe teachers’ general understanding, and analyzed together with the qualitative data by means of thematic analysis. The findings suggest that secondary Korean-English teachers have high appreciation and desire of integrating intercultural dimension in English teaching, but the gap exists between the cognition and the reported practice due to some constraining factors. This study tries to connect teacher cognition of culture teaching, national curriculum, intercultural dimension, their reported practice, and the contextual factors that affect teaching practices, in order to provide the overall and comprehensive picture of English education in Korea. Some suggestions were also made for better future of our English education; regarding culture teaching in English classroom, teacher education and training, the need for teachers’ active attitude in teaching, and the assessment system.